2016
DOI: 10.1111/and.12683
|View full text |Cite
|
Sign up to set email alerts
|

Varicocele is associated with hypogonadism and impaired erectile function: a prospective comparative study

Abstract: We conducted this prospective comparative study to examine the hypothesis that varicocele was associated with hypogonadism and impaired erectile function as reflected in International Index of Erectile Function-5 (IIEF-5) scores as well as nocturnal penile tumescence and rigidity (NPTR) parameters. From December 2014 to December 2015, a total of 130 males with varicocele complaining of infertility or scrotal discomfort and 130 age-matched healthy males chosen from volunteer healthy hospital staff as controls w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
8
0
3
Order By: Relevance
“…And it is a higher incidence of varicocele in the crowd with infertility; a cross‐sectional study showed that the incidence of varicoceles is up to 16.3% in men with fertility requirements who attended an infertility clinic (Dieamant et al ., ), and 26% of infertile men in China suffer from varicocele at present (Zhang et al ., ). Varicocele had a higher risk of heart disease, diabetes, and hyperlipidemia (Wang et al ., ), and caused problems such as pain symptoms, decreased sperm quality, infertility, and even increase in the risk of hypogonadism (Ji & Jin, ). Although the study of varicocele is widespread, the etiology of varicocele remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…And it is a higher incidence of varicocele in the crowd with infertility; a cross‐sectional study showed that the incidence of varicoceles is up to 16.3% in men with fertility requirements who attended an infertility clinic (Dieamant et al ., ), and 26% of infertile men in China suffer from varicocele at present (Zhang et al ., ). Varicocele had a higher risk of heart disease, diabetes, and hyperlipidemia (Wang et al ., ), and caused problems such as pain symptoms, decreased sperm quality, infertility, and even increase in the risk of hypogonadism (Ji & Jin, ). Although the study of varicocele is widespread, the etiology of varicocele remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Однако уменьшение уровня тестостерона сыворот-ки крови коррелирует со временем течения заболе-вания. И указывает на то, что длительное течение варикоцеле приводит к гипогонадизму [11,12]. Но в ранних периодах течения заболевания варикоцеле на базе Харьковского областного клинического центра урологии и нефрологии им.…”
Section: Tatyanatorak@gmailcomunclassified
“…We have read the article “Varicocele is associated with hypogonadism and impaired erectile function: a prospective comparative study” by Ji and Jin (), which was an interesting study investigating the hypothesis that varicocele was associated with hypogonadism and impaired erectile function. In their prospective randomised study, the authors tried to compare serum total testosterone (TT) levels and erectile function between patients with varicocele and control subjects.…”
mentioning
confidence: 99%